Finite element modal analysis and experiment of rice transplanter chassis - Chen, Kaikang; Yuan, Yanwei; Zhao, Bo; Jin, Xin; Lin, Yi; Zheng, Yongjun (International Journal of Agricultural and Biological Engineering, 2022)
The vibration problem during the operation of rice transplanters is the most common phenomenon. In order that the static and dynamic characteristics of the rice transplanter chassis can meet the requirements of more stable operation, the research took the 2ZG-6DK rice transplanter as the research object to carry out a vibration reduction optimization study. In the research, the Pro/Engineer 5.0 software was first used to model the chassis of the rice transplanter. The constructed finite element model was revised by using the structural parameter revision method and the mixed penalty function method. The model was imported into ANSYS Workbench to solve the modal frequency and vibration shape of the rice transplanter chassis. Based on the MAC (modal assurance criterion) criterion, modal tests were carried out to verify the accuracy of the finite element theoretical analysis. Through the analysis of the characteristics of the external excitation frequency, the chassis is structurally optimized to avoid resonance caused by the natural frequency of the chassis falling within the road excitation frequency range. The final optimization results showed that the first four orders of modal frequencies of the chassis were adjusted to 32.083 Hz, 33.751 Hz, 42.517 Hz, and 50.362 Hz, respectively, in the case that the chassis mass was increased by 6.714 kg (8.8%). They all avoid the range of road excitation frequency (10-30 Hz) so that the rice transplanter can effectively avoid the resonance phenomenon during operation. This study can provide a reference for the design and optimization of the chassis structure of transplanter. Keywords: transplanter chassis, vibration, finite element analysis, modal experiment, MAC criterion, optimization design DOI: 10.25165/j.ijabe.20221505.6230 Citation: Chen K K, Yuan Y W, Zhao B, Jin X, Lin Y, Zheng Y J. Finite element modal analysis and experiment of rice transplanter chassis. Int J Agric & Biol Eng, 2022; 15(5): 91–100.